Responsivitas Dinas Koperasi, UKM dan Perindustrian Kabupaten Bantul dalam Menangani UMKM yang Terdampak Pandemi Covid-19 - Kharisman, Aeroen Safis; Atmojo, Muhammad Eko (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2021)
This study aims to see the impact of the pandemic on MSMEs in Bantul Regency. Considering the Covid-19 pandemic has spread throughout the world and is a threat to all countries including Indonesia. DIY is one of the areas that has received the impact of the Covid-19 pandemic, especially in the economic sector, considering that DIY is a tourism object as well as a student city. The decline in the number of MSMEs was due to market demand for goods and services due to the Covid-19 pandemic. This will certainly affect the income and turnover of the business owner. The regional government that runs and regulates regional government plays an important role in handling and reducing the impact of the Covid-19 pandemic. The research was conducted using qualitative research methods, with data obtained from interviews and documentation. The results show that the Bantul Regency KUKMP Office is quite responsive in handling MSMEs affected by the Covid-19 pandemic, especially in terms of attitude and policy making that refers to the problems and complaints of MSMEs in Bantul Regency. However, there is one aspect that must be improved, namely the placement and participation of MSMEs in the service system, in this case the policies and activities or programs that are carried out.